Vesicocolonic Fistula: A Sequela of Missed Blunt Abdominal Injury - Abdulwahab Akanbi Ajape; AbdulLateef Babata; Mustapha Mohammed Kura; Musa Nuhu (Case Reports in Urology)
A case of vesicocolonic fistula secondary to a missed abdominal injury is described. The patient, a 25-year-old male Hausa, Nigerian, was involved in a road traffic accident and sustained head injury with a fractured left femur and a missed blunt abdominal injury. He was referred to us about six months following the injury, on account of failure to micturate, recurrent passage of frequent watery stool, and recurrent fever and weight loss. A suspected diagnosis of intestinovesical fistula was confirmed on micturating cystography. He had a single stage repair of the vesico-colonic fistula. The repair of urethrocutaneous fistula was scheduled for a later date, which he later had. He was discharged but continued with orthopaedic consultation and management.